Cognitive Workload and Workload Transitions Elicit Curvilinear Hemodynamics During Spatial Working Memory - McKendrick, Ryan; Harwood, Amanda (Frontiers in Human Neuroscience, 2019)
Adaptive training and workload management have the potential to drastically change safety and productivity in high-risk fields—including, air-traffic control, missile defense, and nuclear power-plant operations. Quantifying and classifying cognitive load is important for optimal performance. Brain-based metrics have previously been associated with mental workload. Specifically, attenuation of prefrontal activity has been linked to cognitive overload, a cognitive load state associated with degraded task performance. We hypothesized that a similar nonlinearity would be observed for cognitive underload. When underload and overload effects are combined, they should form a cubic function in lateral prefrontal cortex as a function of working memory load. The first of two studies assessed the relationships between spatial working memory load with subjective, behavioral and hemodynamic measures. A cubic function was observed in left dorsolateral prefrontal cortex (LDLPFC; Brodmann’s Area 46) relating working memory load to changes in oxygenated hemoglobin (HbO). The second, two-part study tested the effects of workload transitions to different cognitive load states. Part-one replicated the effects observed in study one and identified transition points for individual performers. Part-two assessed the effects of transitioning to different cognitive load states. Cognitive load state transitions caused a deviation between behavioral measures and induced a significant change in the cubic function relating LDLPFC HbO and working memory load. From these observations, we present a hypothesis associating workload transitions with the disruption of cognitive process integration.